2013
DOI: 10.2337/dc12-1737
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Metabolism After Bariatric Surgery in Grade 3 Obesity

Abstract: OBJECTIVEMalabsorptive bariatric surgery (biliopancreatic diversion and biliointestinal bypass [BIBP]) reduces serum cholesterol levels more than restrictive surgery (adjustable gastric banding [AGB]), and this is thought to be due to greater weight loss. Our aim was to evaluate the changes of cholesterol metabolism induced by malabsorptive and restrictive surgery independent of weight loss.RESEARCH DESIGN AND METHODSIn a nonrandomized, self-selected, unblinded, active-comparator, bicenter, 6-month study, gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 21 publications
6
19
1
2
Order By: Relevance
“…The decrease in LDL, HDL, and total cholesterol levels was significant only in patients who underwent BPD & RYGB. In fact, Benetti et al [19] found that malabsorptive techniques are highly effective in reducing the lipid profile because the absorption of lipids seems to be lowered, which matches with our results because mixed techniques have a malabsorptive component [20]. They also note that variation in cholesterol, HDL and LDL (including sterol) synthesis, catabolism, and absorption is independent of glycaemic control and insulin resistance.…”
Section: Discussionsupporting
confidence: 90%
“…The decrease in LDL, HDL, and total cholesterol levels was significant only in patients who underwent BPD & RYGB. In fact, Benetti et al [19] found that malabsorptive techniques are highly effective in reducing the lipid profile because the absorption of lipids seems to be lowered, which matches with our results because mixed techniques have a malabsorptive component [20]. They also note that variation in cholesterol, HDL and LDL (including sterol) synthesis, catabolism, and absorption is independent of glycaemic control and insulin resistance.…”
Section: Discussionsupporting
confidence: 90%
“…39 In malabsorptive surgery, it has been shown that intestinal cholesterol absorption decreases leading to decreased plasma TC and LDL-C concentrations, accompanied by enhanced hepatic cholesterol synthesis and catabolism. 40 In the present study, the greater reduction in total apoB in GBP compared with SG could be explained by a specific reduction of LDL particle numbers in GBP.…”
Section: Discussionsupporting
confidence: 45%
“…Pihlajamäki et al found a decrease in cholesterol synthesis markers 1 year after both RYGB and AGB but there was a reduction in cholesterol absorption markers only in RYGB while in AGB patients an increase was noted in such absorption markers [23]. Identical results in cholesterol absorption were reported in purely malabsorptive techniques like biliointestinal bypass [17]. RYGB is a mixed restrictive and malabsorptive technique and this last component appears to be a key factor in lowering LDL cholesterol, as it counteracts the compensatory increase in absorption after weight loss.…”
Section: Discussionmentioning
confidence: 69%
“…A still unanswered question is whether this improvement in the lipid profile is merely weight-dependent or otherwise, also results from specificities inherent to the bariatric procedure itself [6]. Current evidence points towards the importance of weight loss [13,17,18].…”
Section: Introductionmentioning
confidence: 98%